2017
DOI: 10.1016/j.ccell.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing CD8+ T Cell Fatty Acid Catabolism within a Metabolically Challenging Tumor Microenvironment Increases the Efficacy of Melanoma Immunotherapy

Abstract: Summary How tumor-infiltrating T lymphocytes (TILs) adapt to the metabolic constrains within the tumor microenvironment (TME) and to what degree this affects their ability to combat tumor progression remain poorly understood. Using mouse melanoma models, we report that CD8+ TILs enhance PPAR-α signaling and catabolism of fatty acids (FAs) when simultaneously subjected to hypoglycemia and hypoxia. This metabolic switch partially preserves CD8+ TILs’ effector functions although co-inhibitor expression increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
444
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 481 publications
(475 citation statements)
references
References 40 publications
13
444
0
Order By: Relevance
“…Indeed, it has been recently shown that, compared to T cells outside the tumour, the expression of the nuclear receptor PPARα is increased in TILs. PPARα induces the expression of genes related to lipid oxidation, such as Cpt1a , which could help TILs to adapt to oxidize FAs from the TME, and thus sustain some degree of effector activity (181). Supplementing vaccination with the PPARα agonist fenofibrate generated cells with enhanced antitumor activity in vivo , supporting the notion that favouring FA catabolism might be best suited to fight tumours in a hypoglycemic environment and generating exciting perspectives for the design of antitumor therapies (181).…”
Section: Localization and Environment May Dictate T Cell Metabolic Prmentioning
confidence: 99%
“…Indeed, it has been recently shown that, compared to T cells outside the tumour, the expression of the nuclear receptor PPARα is increased in TILs. PPARα induces the expression of genes related to lipid oxidation, such as Cpt1a , which could help TILs to adapt to oxidize FAs from the TME, and thus sustain some degree of effector activity (181). Supplementing vaccination with the PPARα agonist fenofibrate generated cells with enhanced antitumor activity in vivo , supporting the notion that favouring FA catabolism might be best suited to fight tumours in a hypoglycemic environment and generating exciting perspectives for the design of antitumor therapies (181).…”
Section: Localization and Environment May Dictate T Cell Metabolic Prmentioning
confidence: 99%
“…[105][106][107][108][109][110] Accordingly, RCD can no longer be perceived as immunogenic when: (1) the intracellular stress responses regulating the emission of ICD-associated DAMPs are pharmacologically or genetically ablated in cancer cells; or (2) when the molecular machinery dedicated to DAMP detection is inhibited or ablated. 13,44,84,91,93,97 Moreover, ICD-driven immunity can no longer operate in the presence of general immunological defects, 111 such as (1) an intrinsically low antigenicity of cancer cells, owing to low levels of TAAs or downregulation of MHC Class I molecules [112][113][114][115][116][117][118][119] ; (2) an increased immunological tolerance of the host, secondary to increased amounts of immunosuppressive cytokines, [120][121][122][123][124][125][126][127][128] or inhibitors of chemotaxis, [129][130][131][132][133][134] increased tumor infiltration by immunosuppressive cell populations, [135][136][137][138][139][140]…”
Section: Introductionmentioning
confidence: 99%
“…There exist efforts in increasing ex vivo the number of central memory CD8 + T cells (from TILs) which are more resistant to exhaustion and therefore effective eliminating tumour (Sukumar, Kishton, & Restifo, 2017). These efforts are mainly directed in modifying TILs metabolism (Shevchenko & Bazhin, 2018;Sukumar et al, 2017;Zhang et al, 2017).…”
Section: Next Generation Of Immunotherapiesmentioning
confidence: 99%